1996
DOI: 10.1111/j.1600-0838.1996.tb00073.x
|View full text |Cite
|
Sign up to set email alerts
|

Physcial exercise and low back pain

Abstract: Health care providers often prescribe exercises as treatment for nonspecific low back pain. However, the effectiveness of this treatment is poorly documented in the literature. While the evidence suggests that exercise in general is beneficial, there is a lack of knowledge about the types, frequency and duration of exercises that should be prescribed and at what stage of injury they are most helpful. In addition, few studies have dealt with exercise treatment alone rather than in combination with other treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(33 citation statements)
references
References 38 publications
1
29
0
3
Order By: Relevance
“…Andererseits mag der klinische Erfolg und zahlreiche wissenschaftliche Belege für kör-perlicher Anstrengung bei einer Reihe internistischer [21,56,64,85] und orthopä-discher [11,43,53,93] und nicht zuletzt neurologischer [70] Erkrankungen auch die therapeutische Einschätzung bei der Migräne beflügelt haben.…”
Section: Zusammenfassungunclassified
“…Andererseits mag der klinische Erfolg und zahlreiche wissenschaftliche Belege für kör-perlicher Anstrengung bei einer Reihe internistischer [21,56,64,85] und orthopä-discher [11,43,53,93] und nicht zuletzt neurologischer [70] Erkrankungen auch die therapeutische Einschätzung bei der Migräne beflügelt haben.…”
Section: Zusammenfassungunclassified
“…At the same time, it is suggested that an inactive or sedentary lifestyle is associated with low back pain complaints. Studies focusing on physical activity and low back pain indicate that the relationship between activity level and low back pain follows a U-shaped curve [11, 14, 15]. Many studies have shown that both too little and too much activity is harmful to spinal health [10, 11, 1620], but the relationship between sports and spinal health has not been adequately clarified.…”
Section: Introductionmentioning
confidence: 99%
“…However, the development (or aetiology) of low back pain is poorly understood and the evidence of the contribution of physical activity to the prevalence, the prevention and management of low back pain is still inconclusive and poorly documented (1,6). Physical activity has been suggested to be both a possible risk factor (20,21,23,26) and a preventive factor (3,15,16,22,32,40) for LBP.…”
Section: Soysal M Et Al: Physical Activity In Patientsmentioning
confidence: 99%